1991
DOI: 10.1111/j.1464-5491.1991.tb02125.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Oxidative Stress to Thrombotic Tendency in Type 1 Diabetic Patients with Retinopathy

Abstract: Increased free radical activity may contribute to thrombosis via effects on platelet aggregation and the prostanoid balance. To investigate this further we studied 15 Type 1 diabetic patients with retinopathy, matched with uncomplicated Type 1 patients for age, duration of diabetes and HbA1, together with matched healthy non-diabetic control subjects. The oxidative effects of free radicals as total diene conjugates and lipid peroxides were measured, together with redox status extracellularly as plasma albumin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 20 publications
2
36
1
1
Order By: Relevance
“…Moreover, non-enzymatic antioxidant elevation also has been observed in the present study after treating diabetic rats with5mg/kg and 10mg/kg of oleuropein. Vitamin Eor α-tocopherol as an essential antioxidant has been proved to be depressed when glucose level is increased in the body (26). The same results been detected in this study, it has been shown a negative correlation between serum glucose level and serum vitamin E levels of diabetic rats treated with oleuropein.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, non-enzymatic antioxidant elevation also has been observed in the present study after treating diabetic rats with5mg/kg and 10mg/kg of oleuropein. Vitamin Eor α-tocopherol as an essential antioxidant has been proved to be depressed when glucose level is increased in the body (26). The same results been detected in this study, it has been shown a negative correlation between serum glucose level and serum vitamin E levels of diabetic rats treated with oleuropein.…”
Section: Discussionsupporting
confidence: 89%
“…These results suggest a mechanism for the altered membrane fluidity and platelet hyperaggregability in diabetes. In both type 1 and type 2 diabetes, the prothrombotic tendency, which includes reduced endothelial cell production of prostacyclin and activators of fibrinolysis, together with increased platelet reactivity, is associated with increased oxidative stress and lipid peroxidation due to excess free radical activity (92,93).…”
Section: Inositol Phospholipid Turnover and Calcium Releasementioning
confidence: 99%
“…Patients with type 2 diabetes have an increased production of free radicals, 1 which can inactivate nitric oxide (NO) 2 and increase diabetic complications. 3 Because endothelial dysfunction is thought to be a precursor of atherosclerosis, a promising therapeutic goal in patients with type 2 diabetes might be to reduce free radical activity.…”
mentioning
confidence: 99%